Significance of Off-hours in Centralized Primary Percutaneous Coronary Intervention Network - Becker, David (Croatian Medical Schools, 2009)
AIM: To analyze the efficacy of a regionally organized primary percutaneous coronary intervention (PCI) network at the Heart Center, Semmelweis University Budapest, part of the “Budapest model,” and the factors that influence it. METHODS: In order to investigate the differences between regular and off-hours patient care in a 24-hour myocardial infarction primary care system, we included 1890 consecutive, unselected patients with ST-segment elevation myocardial infarction and followed them until at least one year. The follow-up was complete for all participants. RESULTS: The difference between regular hours and off-hours mortality was not significant after 30 days (8.6% vs 8.8%, respectively) or after 1 year (15.3% vs 14.7%, respectively). The rate of patients with re-infarction, frequency of re-intervention, and major adverse cardiac events, including death, re-infarction, re-intervention, and coronary artery bypass graft surgery, were similar in both patient groups. The time delay between the onset of chest pain and arrival to the clinic was 5.9 ± 5.8 hours (mean ± standard deviation)during regular hours and 5.2 ± 4.6 hours during off-hours (P = 0.235). Direct transport caused significant decrease in the 30-day and 1-year mortality independent of duty time (7.2% vs 9.9%, P = 0.027; 12.6% vs 16.7%, P = 0.028; respectively). CONCLUSION: Centralized primary PCI network of the “Budapest model” achieved the same level of patient care during both off-hours and regular hours.